(untitled) (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2019)
The Sustainable Development Goals (SDGs) are an opportunity for companies to expand Corporate Social Responsibility (CSR), an initiative that is one of the global efforts to translate sustainable development into something concrete and measurable. In this challenge, companies have been included as a relevant actor to achieve them and today business organizations should be aware of the broad benefits that this entails. In this sense, the objective of the research was to describe the operations of an industrial and engineering services company in the Central-Western region, in such a way as to diagnose whether it carries out corporate social responsibility actions in accordance with the Sustainable Development Goals. (SDGs), included in the CEPAL document Agenda 2030 and the Sustainable Development Goals An opportunity for Latin America and the Caribbean. The results show that even though the company’s key stakeholders were not aware of the existence of the SDGs and their impact on society, their operations incorporate practices and policies aimed at achieving them. Finally, a methodology was suggested into the work recommended by the Official Chamber of Commerce, Industry and Navigation of Valencia, Spain, as a guide for companies to expand their CSR practices, which was adapted according to the characteristics of the company that is the object of the study.